Industrial/Occupational physiotherapy: An international perspective - B. M. Jaholkowski (South African Journal of Physiotherapy, 1983)
An overview of the development and practice of Industrial/Occupational Physiotherapy in Great Britain, Australia, New Zealand, Finland, Sweden and Denmark is given. Training facilities and courses available in each country are mentioned. Barbara McPhee’s recommendations for the development of this field of physiotherapy are quoted as suitable for South Africa.